2018
DOI: 10.1016/j.soildyn.2017.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ground motion characteristics on the optimal single concave sliding bearing properties for base-isolated structures

Abstract: This study examines the influence of ground motion characteristics on the optimal friction properties of single concave sliding bearings employed for the seismic isolation of structural systems. The evaluation of the optimal properties is carried out by considering a non-dimensional formulation which employs the peak ground acceleration (PGA) and the peak ground acceleration-to-velocity (PGA/PGV) ratio as ground motion parameters. A two-degree-of-freedom (2dof) model is employed to describe the isolated system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…In Castaldo and Ripani, the optimal values of the friction coefficient have been provided by means of multivariate nonlinear regression expressions depending on the system properties and on the soil condition in order to minimize the superstructure response with the observation that higher values of the optimal friction coefficient are necessary for soft soil condition. In Castaldo and Tubaldi, the optimal values of the friction coefficient taking into account the influence of the ground motion characteristics by means of the ratio PGA/PGV have been proposed. The seismic performance of bridges isolated with FPS considering different limit states (LSs) has been investigated in Castaldo and Lo Priore …”
Section: Introductionmentioning
confidence: 99%
“…In Castaldo and Ripani, the optimal values of the friction coefficient have been provided by means of multivariate nonlinear regression expressions depending on the system properties and on the soil condition in order to minimize the superstructure response with the observation that higher values of the optimal friction coefficient are necessary for soft soil condition. In Castaldo and Tubaldi, the optimal values of the friction coefficient taking into account the influence of the ground motion characteristics by means of the ratio PGA/PGV have been proposed. The seismic performance of bridges isolated with FPS considering different limit states (LSs) has been investigated in Castaldo and Lo Priore …”
Section: Introductionmentioning
confidence: 99%
“…According to their results, under the near-field earthquakes with fling-step effect, the base isolation proved to be ineffective in terms of reducing base shear, top storey absolute acceleration and maximum inter-storey drift. In a more recent study, Castaldo and Tubaldi (2018) investigated the effects of ground motion characteristics on the optimum friction pendulum properties of seismic isolation systems. It was shown that PGA/PGV is a better indicator of the frequency content of the input ground motion compared to PGA, and can help to provide less scatter predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the static and dynamic behavior of these systems has been deepen analyzed in the recent years also by the experimental point of view [4][5][6][7][8], very few studies about the in-situ behavior of structures equipped with FPIs are available nowadays.…”
Section: Introductionmentioning
confidence: 99%